Cancer Stem Cell-Targeted Therapy: Harapan Baru Terapi Kanker - ARTINI, I GUSTI AYU (Indonesian Journal of Cancer, 2015)
Cancer stem cell (CSC) is subpopulation of tumor cell that posses stem cell properties such as self-renewal capacity and able to produce heterogenous progeny. CSC has been said to be related to cancer development, recurrency, metastasis, and resistance to conventional therapy. Signaling pathway responsible for proliferation and differentiation of CSC are Notch, Hedgehog and Wnt pathway. CSC eradication can be achieved by administering drug or gene-specific molecule targeted to CSC-specific pathway, CSC marker, DNA repair mechanism, apoptosis inhibitor, CSC microenvironment (niche), differentiation therapy, or delivering drug as polymer conjugate (nanocarrier)Â Cancer stem cell (CSC) adalah subpopulasi sel tumor yang memiliki properti stem cell, yaitu memiliki kemampuan memperbarui diri dan dapat menghasilkan turunan yang heterogen. Keberadaan CSC dikatakan berkaitan dengan perkembangan kanker, rekurensi, metastasis, dan resistansi terhadap terapi konvensional. Jalur sinyaling yang berperan dalam proliferasi dan diferensiasi CSC adalah jalur Notch, Hedgehog, dan Wnt. Eradikasi CSC dapat dicapai dengan obat atau molekul spesifik yang menarget jalur sinyaling CSC, penanda CSC, mekanisme perbaikan DNA, inhibitor apoptosis, lingkungan mikro CSC (niche), terapi diferensiasi, atau mengirim obat dalam bentuk konjugat polimer (nanocarrier).